Hubungan antara School Safety dan Respons Bystander Bullying pada Siswa SMA: Studi Perbandingan Desa-Kota - Paranti, Sherly Mega; Takwin, Bagus (Jurnal Psikologi : Media Ilmiah Psikologi, 2022)
Along with the increasing incidence of bullying in the school environment, it is necessary to conduct an in-depth study on how to suppress the incidence of bullying. Bystander bullying is known to have an important role in suppressing bullying, especially when the bystander shows behavior to help and defend the victim. Previous studies have found that the perceived sense of school safety is related to the tendency of students to help victims of bullying. This study wants to look further into the relationship between school safety and bystander bullying responses by comparing the context of rural and urban schools. This study predicts that rural school students tend to be more willing to help victims, regardless of their perception of a school safety. A total of 109 high school students in the Jakarta and surrounding areas, which consist of 75 rural school students and 34 urban school students, participated in this study by filling out a series of questionnaires that measured school safety and the tendency to respond to bullying incidence. The results of this study show that rural school students tend to be more willing to help victims of bullying than urban school students. In addition, it was found that there was no relationship between perceptions of school safety and the tendency to help victims of bullying in rural and urban schools. The results of this study have implications in determining the appropriate intervention between rural and urban schools in encouraging students to be more willing to help victims of bullying